Expectations and Stability with Gross Complements - Tarr, D. G. (Review of Economic Studies, 1978)
Journal Article Expectations and Stability with Gross Complements Get access David G. Tarr David G. Tarr Federal Trade Commission, Washington Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 3, October 1978, Pages 617–620, https://doi.org/10.2307/2297263 Published: 01 October 1978 Article history Received: 01 February 1976 Accepted: 01 September 1977 Published: 01 October 1978